PROMOSI PENGEMBANGAN KREATIVITAS PESERTA DIDIK DALAM PEMBELAJARAN - St. Nurjannah Yunus Tekeng (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
Every individual has the potential to be creative. Creativity is more than the use of someone’s imagination. This is a lifestyle, personality characteristic, and ways of understanding the world.Creativity depends on two main factors namely here-dity (nature) and the influence of environment (nurture). To support the develop-ment of this students’ creative potential, there is a need for an instructional design that facilitate the active participation of students in explorating their potential, trying out, examining, hypothesizing, and finding out a new creative idea. Be-sides, instructors should develop openness and respecting students thinking. Do-ing this is a way to respond tothedemand of the era.